STATUS GIZI DAN STATUS MENSTRUASI REMAJA PUTRI DI KECAMATAN PELAWAN KABUPATEN SAROLANGUN - Dini Junita (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
ABSTRACT Monitoring the health status of young women is important. This study aims to identify and analyze the relationship between nutritional status and menstrual status in adolescent girls. This study used a cross sectional study design in SMA N 8 and SMK N 7 in Pelawan District, Sarolangun Regency. A total of 144 young women who met the criteria were taken by total accidental sampling. Nutritional status was determined based on Body Mass Index (BMI) by age. While menstrual status data was obtained by direct interview with respondents using a questionnaire. The data analyzed by univariate and bivariate (correlation test). Based on the results of the study obtained a description of the nutritional status of respondents, namely 91.67% have normal nutritional status and the remaining 8.33% is not normal, namely undernutrition and over nutrition. The majority of respondents' menstrual status is not normal, as many as 118 people (81.94%). Respondents who experienced abnormal menstrual cycles were 61 respondents (42.36%), 56 respondents (38.89%) had abnormal menstrual duration or more than 7 days, 75 respondents (52.08%) claimed to experience menstrual disorders such as nausea, stomach pain and headaches which results in inhibition of activity. There is not enough evidence to state the relationship of nutritional status to the menstrual status of adolescent girls. Need further research related to the role of nutrients physiologically during menstruation.ABSTRACT Monitoring the health status of young women is important. This study aims to identify and analyze the relationship between nutritional status and menstrual status in adolescent girls. This study used a cross sectional study design in SMA N 8 and SMK N 7 in Pelawan District, Sarolangun Regency. A total of 144 young women who met the criteria were taken by total accidental sampling. Nutritional status was determined based on Body Mass Index (BMI) by age. While menstrual status data was obtained by direct interview with respondents using a questionnaire. The data analyzed by univariate and bivariate (correlation test). Based on the results of the study obtained a description of the nutritional status of respondents, namely 91.67% have normal nutritional status and the remaining 8.33% is not normal, namely undernutrition and over nutrition. The majority of respondents' menstrual status is not normal, as many as 118 people (81.94%). Respondents who experienced abnormal menstrual cycles were 61 respondents (42.36%), 56 respondents (38.89%) had abnormal menstrual duration or more than 7 days, 75 respondents (52.08%) claimed to experience menstrual disorders such as nausea, stomach pain and headaches which results in inhibition of activity. There is not enough evidence to state the relationship of nutritional status to the menstrual status of adolescent girls. Need further research related to the role of nutrients physiologically during menstruation.